THE SHIFT OF JIHAD: BETWEEN IDEAL AND HISTORICAL CONTEXT - Yamamah, Ansari (Journal of Al-Tamaddun, 2013)
Jihad is one of the most inspiring and most controversial notions in the Quran. In one perspective, jihad offers an eschatological promise of eternal happiness. On the other hand, it shows an impact or phenomenon which has a gigantic effect of destroying human administrations. This paper examines the meaning of jihad and its application between ideal and historical context. This paper concludes that the misunderstanding of jihad should be avoided by exploring the true meaning of this notion which not only referring to jihad bi al-qital. However, it has wider meaning which relates to human daily life.